Pengaruh Kesadaran Halal, Harga, dan Promosi terhadap Keputusan Pembelian Shopee Food pada Konsumen Muslim Generasi Z di Bandung Raya - Dwina, Rebeca; Sarasi, Vita (SM Institute, 2025)
This study aims to the influence of halal awareness, price, and promotion on purchase decisions for Shopee Food among Generation Z Muslim consumers in Bandung Raya. With more than 87% of Indonesia's population being Muslim, understanding how these factors influence consumption behavior, particularly among Generation Z who are the primary users of online food delivery services, is crucial. This research employs a quantitative approach with a survey method. The research sample consists of 160 respondents, all Muslim Generation Z Shopee Food consumers in Bandung Raya, selected using purposive sampling and data collected via questionnaires. The analysis technique used in this study is Structural Equation Modeling (SEM), assisted by Smart Partial Least Square 3.2.9 (SmartPLS 3.2.9) software. The results indicate that each independent variable (halal awareness, price, and promotion) has a positive and significant effect on the dependent variable, namely purchase decisions. Keywords : Halal Awareness, Price, Promotion, Purchase Decision, Shopee Food